Innovative intelligence: a three-component vector model - Vladimir Chernoles; Dinara Khudaynazarova (Studia Ecologiae et Bioethicae)
This paper considers the limited nature of the existing psychodiagnostic procedures designed to make an objective evaluation of human intelligence and the level of its readiness for innovative activity. The author introduces the concept of innovative intelligence and offers its three-vector model consisting of analytical, creative, and practical intelligence. This approach can serve as the basis for the optimum formation of a creative group, its role structurization, and rating of the level of readiness of a person for innovative activity.